Restricted and repetitive behaviors and their developmental and demographic correlates in 4–8-year-old children: A transdiagnostic approach - Keating, Jennifer; Van Goozen, Stephanie; Uljarevic, Mirko; Hay, Dale; Leekam, Susan R. (Frontiers in Behavioral Neuroscience, 2023)
Background: Restricted and repetitive behaviors (RRBs) are a broad class of behaviors characterized by frequent action repetition and intense preference for sameness. Research has predominantly focused on RRBs in diagnosed clinical groups, particularly in autism spectrum disorder and genetic disorders. Using a transdiagnostic approach, the current study examined RRBs in a diverse sample of children in relation to developmental and demographic correlates, (age, language, non-verbal ability, child anxiety, gender, socioeconomic status). Separate analyses examined two RRB subtypes; repetitive sensory and motor behaviors (RSMB) and insistence on sameness (IS). Method: Children (N=260, age 4-8 years, 174 male, 86 female) in mainstream schools identified by teachers as having behavioral, emotional, and/or cognitive difficulties, were assessed using the Repetitive Behavior Questionnaire-2 (RBQ-2), the British Picture Vocabulary Scale (BPVS), Lucid Ability Scale, the Welsh Index of Multiple Deprivation (WIMD) and the Screen for Child Anxiety Related Emotional Disorders (SCARED). Recruitment excluded diagnosed clinical conditions. The Strengths and Difficulties Questionnaire (SDQ) was used to assess children’s difficulties. Results: RRB scores were of high frequency and the scores for the IS were higher than for RSMB. Severity of anxiety symptoms and male gender were significantly associated with both RRB subtypes, and younger age and SES scores were associated with IS. Elevated RRB total and subtype scores were significantly related to SDQ scores for emotion, conduct, hyperactivity, and peer-relations. Discussion: The study provides first evidence of RRBs in a diverse sample of young children with emerging difficulties in behavior, cognition and/or emotion. The results contribute to proposals about psychological development in RRB and indicate that RRBs are best represented on a continuum of severity found across children in the early school years. The results support previous findings of a relation between RRB and anxiety reported in clinical samples and importantly, they indicate that it is time to move beyond the study of categorically defined groups and consider correlates of RRBs that include broad indices of mental health and well-being.